2017
DOI: 10.1016/j.dark.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Quantum deformation of quantum cosmology: A framework to discuss the cosmological constant problem

Abstract: We endorse the context that the cosmological constant problem is a quantum cosmology issue. Therefore, in this paper we investigate the q-deformed Wheeler-DeWitt equation of a spatially closed homogeneous and isotropic Universe in the presence of a conformally coupled scalar field. Specifically, the quantum deformed Universe is a quantized minisuperspace model constructed from quantum Heisenberg-Weyl U q (h 4 ) and U q (su(1, 1)) groups. These intrinsic mathematical features allow to establish that (i) the sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 124 publications
(120 reference statements)
0
11
0
Order By: Relevance
“…As remarked in the introduction, SU q (N ) bosons are strictly related to GUP [42]. This fact represents a suggestive hint about the basic role played by quantum groups in the fundamental descriptions of nature (see also [3,4,5,6,7,8]).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…As remarked in the introduction, SU q (N ) bosons are strictly related to GUP [42]. This fact represents a suggestive hint about the basic role played by quantum groups in the fundamental descriptions of nature (see also [3,4,5,6,7,8]).…”
Section: Discussionmentioning
confidence: 73%
“…Quantum groups, originally introduced in connection with Quantum Inverse Scattering Method and Yang-Baxter equation [1], nowadays represent a widespread mathematical framework: their applications cover various areas of physics, including condensed matter physics [2] and quantum gravity [3,4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding that the parameter γ has dimension of inverse of length (as pointed out in [25]), then γ would be a new fundamental constant of theory. However, as addressed in [26], the origin of this unwanted new constant is the effective matter field Lagrangian in action (28). If we use a "real" matter field, for example a scalar field or the Maxwell's field Lagrangian instead of ρ in (28), then the value of γ will be fixed to only following two acceptable values…”
Section: Fractional Quantum Flrw Cosmology: a Simple Case Studymentioning
confidence: 99%
“…On a similar line of reasoning, q-deformed formulations of Loop Quantum Gravity (LQG) were proposed along the years [8][9][10][11], which naturally incorporate the cosmological constant. This relationship was even used in different models [12]. It has been also shown that the quantum group structure of the κ-Poincaré is the natural symmetry for effective field theories, emerging from discrete gravity theories coupled to matter [13], and for noncommutative description of the spacetime [14][15][16].…”
Section: Introductionmentioning
confidence: 98%